PERTIMBANGAN HAKIM DALAM PEMIDANAAN PELAKU TINDAK PIDANA BIDANG PANGAN - Sudirman Laia (LPPM Universitas Nias Raya, 2025)
Nowadays, there are more and more cases of food crimes and there are also many punishments for food criminals that are decided by the courts and have legal force that is not in accordance with laws and regulations. One of the said judgments is judgment number 1130/Pid.B/2016/PN.Bdg. In the said judgment, the offender was convicted under Article 135 jo. Article 71 paragraph (2) letter a of the Food Act carries the threat of imprisonment or fines, but the judge imposes imprisonment along with the fine. Therefore, this study aims to find out and analyze the judge's considerations in the punishment of perpetrators of food crimes (study of verdict number 1130/Pid.B/2016/PN.Bdg). This research uses a type of normative legal research, using secondary data and methods of approaching laws and regulations, case approaches, and analytical approaches, as well as using qualitative data analysis. Based on the findings of research and discussion, it can be concluded that the judge's consideration in sentencing perpetrators of food crimes (study decision number 1130/Pid.B/2016/PN.Bdg) consists of juridical and non-juridical considerations. Juridically, the perpetrator has been proven to have committed a criminal act as referred to in Article 135 jo. Article 71 paragraph (2) letter a of the Food Act. Non-juridically, there is a burdensome reason for the punishment for the perpetrator, namely that the perpetrator has been convicted. Therefore, the imposition of imprisonment along with the fine in the judgment is a punishment for the perpetrator. However, in this article, there is a threat of a fairly high penalty, namely a maximum of 2 (two) years in prison or a maximum fine of Rp 4,000,000,000 (four billion rupiah). In order to impose a sentence on the perpetrator, the judge can impose a maximum prison sentence or a maximum fine, so that the judge's decision does not seem to deviate from the Food Law. The researcher suggested that the judge in passing each conviction in accordance with the criminal threat in the Food Act.